Diferentes maneiras de definir a função logarítmica natural - Garcia, Eduardo Granado [UNESP] (2014)
The main objective of this paper is to present difierent forms of defining the natural logarithm function. And, more specifically, start from the exponential function; its inverse; as an area of a region on the plane and finally as the limit in a real number sequence. Besides that, on the last chapter we aimed at doing an analysis of some issues that influence the teaching of logarithm in Basic Education. As theoretical basis we have employed some sources that approach the process of Mathematics Teaching in our country as well as oficial directives such as the PCN - National Curricular Parameters and the Sao Paulo State Oficial Educational Curriculum. Based on the latter we have done an analysis of the teaching sequences that make up the material which is made available to the students of the state public schools and veri ed the kind of approach employed for the teaching of logarithms